Parenting Strategies to Deal with Children’s Anxiety: Do Parents Do What They Say They Do? - Beato, Ana (2022)
Parents’ perceptions about their strategies to deal with children’s anxiety have been minimally explored. Based on a mixed-method approach, the current study compared the strategies that parents said they use more frequently to deal with their child’s anxious behaviors and the strategies they actually used during two mildly anxio genic interactions with their child. Forty-two parents of children with anxiety disorders, aged 9–12 years, partici pated in the study. Semi-structured interviews were administered to identify parental perceptions about their strategies to deal with their children’s anxiety. Subse quently dyadic interactions were observed and coded by two independent coders. We found discrepancies relating to four strategies. Significantly more parents used strategies based on overinvolvement and anxious behavior during the interactions than had been reported by them in the inter views. In contrast, reassurance and reinforcement of avoidance/dependence were used in interactions by fewer parents than would be expected, according to the interviews. Relevant implications for assessment and interven tion with families of anxious children are suggested.